2016
DOI: 10.1038/srep35778
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic Responses of Arabidopsis Suspension Cells to Bicarbonate under Light and Dark Conditions

Abstract: Global CO2 level presently recorded at 400 ppm is expected to reach 550 ppm in 2050, an increment likely to impact plant growth and productivity. Using targeted LC-MS and GC-MS platforms we quantified 229 and 29 metabolites, respectively in a time-course study to reveal short-term responses to different concentrations (1, 3, and 10 mM) of bicarbonate (HCO3−) under light and dark conditions. Results indicate that HCO3− treatment responsive metabolomic changes depend on the HCO3− concentration, time of treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…A. thaliana (var. Landsberg erecta (LER) suspension cells, kindly gifted by Dr. Joshua L. Heazlewood, University of Western Australia, Australia) were maintained and sub-cultured according to a previous method (Misra et al, 2016 ). Briefly, the cell culture was grown in 250-ml flasks under light at 130 μmol m −2 s −1 on an orbital shaker at 120 rpm, 22°C, and was sub-cultured weekly.…”
Section: Methodsmentioning
confidence: 99%
“…A. thaliana (var. Landsberg erecta (LER) suspension cells, kindly gifted by Dr. Joshua L. Heazlewood, University of Western Australia, Australia) were maintained and sub-cultured according to a previous method (Misra et al, 2016 ). Briefly, the cell culture was grown in 250-ml flasks under light at 130 μmol m −2 s −1 on an orbital shaker at 120 rpm, 22°C, and was sub-cultured weekly.…”
Section: Methodsmentioning
confidence: 99%
“…A metabolomic analysis performed on Arabidopsis cultured cells incubated in the dark or light showed that although most of the metabolites are common to both conditions, c . 30 metabolites, mainly related to pyridine metabolism or folate biosynthesis, differ under each light or dark condition, respectively (Misra et al ., 2016). Comparative nontargeted metabolomic analyses between light‐ and dark‐grown roots showed a large number of light‐induced metabolites (Silva‐Navas et al ., 2016), and it is possible that some of them could be secreted to the exterior.…”
Section: Root–biotic Interactions May Be Influenced By Lightmentioning
confidence: 99%
“…It has been reported that exposure to different intensities of red : blue ratios of light alters the amount of benzoic acid, salicylic acid, ferulic acid, gallic acid, and tannic acid secreted from the root surface area of hydroponic lettuce (Zhou et al, 2020). A metabolomic analysis performed on Arabidopsis cultured cells incubated in the dark or light showed that although most of the metabolites are common to both conditions, c. 30 metabolites, mainly related to pyridine metabolism or folate biosynthesis, differ under each light or dark condition, respectively (Misra et al, 2016). Comparative nontargeted metabolomic analyses between lightand dark-grown roots showed a large number of light-induced metabolites (Silva-Navas et al, 2016), and it is possible that some of them could be secreted to the exterior.…”
Section: Root-biotic Interactions May Be Influenced By Lightmentioning
confidence: 99%
“…Since its introduction by Nicholson et al in 1999, metabolomics has been extensively applied to various fields of science in the post-genomic era, such as agricultural research [6,7,8,9,10]. …”
Section: Introductionmentioning
confidence: 99%